2020
DOI: 10.1097/md.0000000000021903
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of traditional Chinese medicine on mild active ulcerative colitis

Abstract: Introduction: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) characterized by a relapsing-remitting course owing to recurrent intestinal inflammation. UC often has symptoms such as intermittent rectal bleeding, diarrhea, and abdominal pain. As the precise etiology of UC has not completely clarified, UC has become a public health challenge worldwide. According to an epidemiological survey, there were about 350,000 new cases of IBD in China from 2005 to 2014. By 2025, the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…TCM formulations are the promising choice since many TCM formulations have been proven to effectively treat UC in the Chinese population for centuries, and they are all biological organics and natural materials mostly harmless to humans and animals. 31,32 The present study aimed to seek a safe and effective TCM formulation for the treatment of UC and explore its action mechanism. BLG is a well-known TCM formulation prescribed for influenza treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TCM formulations are the promising choice since many TCM formulations have been proven to effectively treat UC in the Chinese population for centuries, and they are all biological organics and natural materials mostly harmless to humans and animals. 31,32 The present study aimed to seek a safe and effective TCM formulation for the treatment of UC and explore its action mechanism. BLG is a well-known TCM formulation prescribed for influenza treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative therapies represented by TCM have been reported increasingly in recent years [24][25][26][27]. In China, TCM prescriptions based on Han Re Bing Yong Fa have been widely used in UC treatment, with preferable efficacy and safety [28][29][30]. Basic studies demonstrated that modified BXXXD, a formula similar to GJHQHLRSD, can effectively alleviate UC as well as relieve depression and UC through targeting VEGFA, TNF, STAT3, EGFR, and others [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of IBD is rapidly increasing in China ( Ananthakrishnan et al, 2020 ). Chinese medicines might be an optional therapeutic method for patients ( Zhang et al, 2013 ; Kou et al, 2020 ; Ye et al, 2020 ). More and more Chinese herbal medicines and relative products might be taken along with vitamin D supplements when treating IBD.…”
Section: Discussionmentioning
confidence: 99%